Comparative pedagogy in the context of global changes - Saidova, Kamola (MMIT Proceedings, 2025)
The research is devoted to analyzing the problems and prospects of pedagogical comparative studies in the era of global changes, focusing on the impact of digitalization, cultural diversity, and the transformation of educational practices on the development of pedagogical science. The author emphasizes the need to modernize methodological approaches for a deeper analysis of educational systems in different countries, arguing that it is important to move from simple comparison to understanding the values and meanings of education within specific cultural contexts. The relevance of the study lies in the growing need for new analytical tools that reflect the complexity and diversity of globalization processes in modern education.